What makes a successful export? - Holger Görg; Richard Anthony Kneller; Balázs Muraközy (Kiel Institute for the World Economy (IfW), 2008)
We analyse a very rich and unique panel database which provides information on exports at the firm-product level. A stylised fact in the data is that many firms add as well as drop products from the export mix in any given year. Motivated by recent theory we investigate what determines the survival of products in the export mix. Estimating hazard models we find evidence that is consistent with the view that characteristics of the product as well as that of the firm matter. This suggests, in line with theory, that there are firm- as well as firm-product specific competencies that are important for shaping firms' export mix.
Keywords: F12; F14; 330; Product level; Product survival; Competencies; Export mix; Exportindustrie; Produktpolitik; Erfolgsfaktor; Ungarn